2020
DOI: 10.1111/dom.14167
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a low glycaemic index diet on reducing day‐long glycaemia in healthy young adults: A randomized crossover trial

Abstract: Aim: To compare the effect of a low glycaemic index (LGI) diet on reducing day-long glycaemia with a macronutrient-matched high glycaemic index (HGI) diet, using customized meal delivery to ensure compliance. Materials and Methods: We conducted a single-blinded, randomized crossover trial in 14 healthy adults (57% female) with a mean ± SD age of 21.6 ± 1.7 years. A flash glucose monitoring sensor was installed on the subjects on day 1 to capture the interstitial glucose level every 15 minutes for 14 days. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Short-term intervention studies [ 32 ] and epidemiological and prospective studies have consistently shown an association between wholegrain consumption and a reduced mortality and metabolic disease risk [ 33 , 34 ]. A short-term study using continuous glucose monitoring showed that young healthy adults following a low GI diet had lower average day-long glycemia compared with a macronutrient-matched high GI diet, indicating the use of low GI diets to reduce the risk of developing glucose intolerance [ 35 ]. The use of GI for the classification of carbohydrate-rich foods has been endorsed by the FAO/WHO, who recommended that the GI of foods should be considered together with information about food composition to guide food choices [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Short-term intervention studies [ 32 ] and epidemiological and prospective studies have consistently shown an association between wholegrain consumption and a reduced mortality and metabolic disease risk [ 33 , 34 ]. A short-term study using continuous glucose monitoring showed that young healthy adults following a low GI diet had lower average day-long glycemia compared with a macronutrient-matched high GI diet, indicating the use of low GI diets to reduce the risk of developing glucose intolerance [ 35 ]. The use of GI for the classification of carbohydrate-rich foods has been endorsed by the FAO/WHO, who recommended that the GI of foods should be considered together with information about food composition to guide food choices [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic reduction of the dietary glycemic index (GI) could be an important approach to improve postprandial glucose response. It has been shown previously that replacing rapidly digestible, high-GI foods by slowly digestible, low-GI foods contributes to reduced postprandial glycemia and insulinemia and lowers glycemic variability (8)(9)(10)(11). Moreover, there is sufficient evidence that a frequent consumption of high-GI foods is associated with an increased risk of cardiometabolic diseases when compared to a diet rich in low-GI foods (12,13).…”
Section: Introductionmentioning
confidence: 99%